1997
DOI: 10.1093/bja/78.6.675
|View full text |Cite
|
Sign up to set email alerts
|

Intraperitoneal lignocaine for pain relief after total abdominal hysterectomy

Abstract: In this preliminary randomized study, we have measured pain scores at rest and on movement, 24 and 48 h after operation in 19 control patients, who received 50 ml of saline i.p., and in 20 test patients, in whom 50 ml of saline solution containing lignocaine 200 mg and adrenaline 1:500,000 were instilled into the peritoneal cavity after total abdominal hysterectomy. We found that there was no difference in linear analogue scores for nausea, pain on movement or morphine consumption after operation between the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 6 publications
0
24
0
Order By: Relevance
“…Bupivacaine, levobupivacaine, lidocaine and ropivacaine have been used intraperitoneally in varying doses to achieve analgesia in various laparoscopic surgeries. [9][10][11][12] In the studies, after the laparoscopic surgeries, the intraperitoneal local anesthetics are found to be very effective for the decrease in postoperative pain. 13 This non-invasive method has a minimum risk and it can be easily applied.…”
Section: Resultsmentioning
confidence: 99%
“…Bupivacaine, levobupivacaine, lidocaine and ropivacaine have been used intraperitoneally in varying doses to achieve analgesia in various laparoscopic surgeries. [9][10][11][12] In the studies, after the laparoscopic surgeries, the intraperitoneal local anesthetics are found to be very effective for the decrease in postoperative pain. 13 This non-invasive method has a minimum risk and it can be easily applied.…”
Section: Resultsmentioning
confidence: 99%
“…Campagnol found that a single IP injection of bupivacaine (5 mg/kg) resulted in lower pain scores for 1 hour after ovariohysterectomy in dogs. Others have demonstrated that human patients undergoing various laparoscopic or surgical procedures such as cholecystectomy, gynecological procedures, gastric bypass, or banding have an overall reduction in abdominal pain and postoperative opioid use when given IP injections of local anesthetics . Although others have reported no benefit of IP local anesthetic administration, there are no reports of significant complications of injection.…”
Section: Discussionmentioning
confidence: 99%
“…A single prospective, randomized, double‐blind trial evaluated the effect of continuous IP local anesthetic infusion on postoperative pain following laparoscopic surgery in adults . Although sample size was small, the authors found that continuous IP infusion of bupivacaine, compared to a saline placebo, resulted in reduced pain from 6 to 48 hours postoperatively when combined with traditional parenteral morphine administration.…”
Section: Discussionmentioning
confidence: 99%
“…21 However, our clinical findings support a lack of analgesic efficacy after laparoscopic cholecystectomy 9,22,23 or after major gynecologic surgery. [2][3][4] Of note, one of the few studies to report efficacy provided a prolonged IP infusion via a catheter 8 and there is some evidence that high concentrations administered before dissection are more effective. 10 Although small doses of IP morphine are not effective after laparoscopic sterilization, 24 Colbert et al 11 reported improved analgesia when meperidine 50 mg was added to IP bupivacaine 100 mg and epinephrine, rather than injected IM.…”
Section: Discussionmentioning
confidence: 99%
“…1 Evidence for the effectiveness of IP LA is less compelling when used for more extensive intraabdominal and pelvic laparoscopic surgery. Trials involving major gynecologic surgery have been disappointing, mostly showing no benefit [2][3][4] or, at best, a short-term and modest effect. [5][6][7] Only one trial reported a significant reduction in morphine consumption and also less postoperative nausea and vomiting (PONV).…”
mentioning
confidence: 99%